Experimental study on effect of freeze-thaw cycles on dynamic mode-Ι fracture properties and microscopic damage evolution of sandstone. (17th February 2023) - Zhang, Rongrong; Yang, Yi; Ma, Dongdong; Ping, Qi
Highlights: The microscopic damage evolution characteristics of F-T damaged sandstone is studied. The relationship between dynamic fracture toughness and F-T cycle number is investigated. The F-T damage factor is defined based on the variation in wave impedance of sandstone. Abstract: The investigation of dynamic fracture characteristics of sandstone after freeze-thaw (F-T) treatments is of great significance for the optimization of blasting parameters and stability analysis of rock masses engineering in cold or high-elevation regions. In the present study, the P-wave velocity, porosity, T 2 spectrum curve, and micromorphology of sandstone specimen after different F-T cycles were measured using nuclear magnetic resonance (NMR) and scanning electron microscopy (SEM) techniques. The F-T damage factor was defined according to the reduction in wave impedance. Moreover, the dynamic mode-Ι fracture test was carried out using notched semicircular bend (NSCB) sandstone specimen. Meanwhile, the fracture process of NSCB specimen was captured by adopting a high-speed photography system. Test results show that F-T cycles can irreversibly deteriorate the microscopic pore structure and the cementation between mineral particles, which is manifested by an increase in the proportion of macropores and mesopores. The dynamic fracture pattern of sandstone specimen is affected by the coupling of F-T cycle number and loading pressure. Furthermore, the dynamic fracture toughness of sandstone constantly increases with the increase of loading rate at a specified F-T cycle number, while the F-T cycle treatment has a significant weakening effect. There has a negative exponential correlation between dynamic fracture toughness and F-T damage factor.